equação √(x-1+√(2x-2)) =2
conforme anexo
Anexos:
![](https://pt-static.z-dn.net/files/dcc/500c277359a69c36b9d9aedb67b8f3e2.jpeg)
Soluções para a tarefa
Respondido por
1
Elevando os 2 lados ao quadrado:
x-1 +
=4
5-x = raiz(2x-2)
Eleva os 2 lados ao quadrado:
(5-x)² = 2x -2
x² -10x +25 = 2x -2
x² -12x +27 = 0
Báskara:
x'=9 x''=3
x-1 +
5-x = raiz(2x-2)
Eleva os 2 lados ao quadrado:
(5-x)² = 2x -2
x² -10x +25 = 2x -2
x² -12x +27 = 0
Báskara:
x'=9 x''=3
Perguntas interessantes
Matemática,
11 meses atrás
Artes,
11 meses atrás
Filosofia,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás